Analysis Prevalence and Effectiveness of the Stunting Management Intervention Program for Toddlers in Bogor City - Binta Agung Putra Wibawa; Afida Nurul Yasmin; Fauzan Syahrul Jihad; Karlena Indriani; Monikka Nur Winnarto (Jurnal Infortech, 2026)
Stunting remains a major public health challenge in Indonesia. Although various intervention programs have been implemented, more effective strategies are needed to achieve the targeted reduction in prevalence. Based on the findings of this study, the City of Bogor reduced its stunting prevalence from 3.32% in 2022 to 2.35% in 2024. This study aimed to identify the key factors contributing to the success of stunting intervention programs using a Root Cause Analysis (RCA) approach, focusing on program implementation at the sub-district level. The methods included Exploratory Data Analysis (EDA) to examine spatial-temporal trends in stunting prevalence and RCA based on secondary data, program documents, and interpretation of EDA findings. Potential causes affecting program performance were categorized using a fishbone (Ishikawa) framework. The results showed that the decline in stunting prevalence was accompanied by an increase in child weighing coverage from 88.83% to 99.49% and a reduction in disparities across sub-districts. RCA identified six key factors influencing program effectiveness: (1) the number and competence of Posyandu cadres relative to community awareness; (2) standardization of procedures and cross-sectoral coordination; (3) availability of anthropometric measurement equipment; (4) targeted distribution of supplementary feeding (PMT) and vitamins; (5) family participation and nutritional literacy; and (6) data accuracy and timely follow-up of cases. These factors were derived from program documents, secondary data interpretation, and fishbone-based categorization. The findings provide evidence-based recommendations for sustaining stunting reduction through more targeted interventions.